Ocular Involvement in Children with Inflammatory Bowel Disease. - Naviglio, Samuele; Parentin, Fulvio; Nider, Silvia; Rassu, Nicolò; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2017)
BACKGROUND: Data on ocular manifestations of inflammatory bowel disease (IBD) in children are limited. Some authors have reported a high prevalence of asymptomatic uveitis, yet the significance of these observations is unknown and there are no recommendations on which ophthalmologic follow-up should be offered. METHODS: Children with IBD seen at a single referral center for pediatric gastroenterology were offered ophthalmologic evaluation as part of routine care for their disease. Ophthalmologic evaluation included review of ocular history as well as slit-lamp and fundoscopic examination. Medical records were also reviewed for previous ophthalmologic diagnoses or complaints. RESULTS: Data from 94 children were included (52 boys; median age 13.4 yr). Forty-six patients had a diagnosis of Crohn's disease, 46 ulcerative colitis, and 2 IBD unclassified. Intestinal disease was in clinical remission in 70% of the patients; fecal calprotectin was elevated in 64%. One patient with Crohn's disease had a previous diagnosis of clinically manifest uveitis (overall uveitis prevalence: 1.06%; incidence rate: 0.3 per 100 patient-years). This patient was also the only one who was found to have asymptomatic uveitis at slit-lamp examination. A second patient had posterior subcapsular cataract associated with corticosteroid treatment. No signs of intraocular complications from previous unrecognized uveitis were observed in any patient. CONCLUSIONS: Children with IBD may have asymptomatic uveitis, yet its prevalence seems lower than previously reported, and it was not found in children without a previous diagnosis of clinically manifest uveitis. No ocular complications from prior unrecognized uveitis were observed.
Keywords: Adolescent; Child; Child, Preschool; Feces; Female; Humans; Inflammatory Bowel Diseases; Italy; Leukocyte L1 Antigen Complex; Male; Remission Induction; Uveitis